Psychological and psychopathological scales administered to incarcerated adult (male and female) firesetters and offending controls - Gannon, Theresa A. (UK Data Service, 2017)
Dataset resulting from batteries of questionnaires administered to incarcerated firesetters and offending control participants. Each week, criminal firesetting costs England and Wales over £42 million and results in 65 casualties (Arson Prevention Bureau, 2009). Astonishingly, professionals hold little knowledge of firesetters. This research will examine types of male firesetters, their treatment needs, and using this information, will develop, implement, and evaluate the first standardised treatment programme for firesetters. In Stage 1, firesetters and non-firesetter offenders will complete a battery of questionnaires designed to assess characteristics associated with firesetting. Here, statistical procedures will highlight natural subgroups of firesetters who share similar characteristics. Then, firesetters and non-firesetters will be compared on the questionnaires to see which characteristics differentiate firesetters from other offenders. In Stage 2, a specialist group treatment programme for firesetters will be developed and implemented in prisons. Questionnaires established at Stage 1 will examine each firesetter's deficits before entering the programme, and then will be used to assess improvements on these deficits post treatment. Any improvements made by firesetters in the new treatment will then be compared with the performance of a comparison group of firesetters who do not attend this treatment. The results of this research programme will highlight the main characteristics of firesetters and whether or not these can be treated successfully.